UPAYA MENINGKATKAN KECERDASAN EMOSIONAL ANAK MELALUI KEGIATAN MENDENGARKAN MUSIK RELAKSASI - Uliah Ulfah; Teti Ratnasih; Syamiyah Syamiyah (UIR PRESS, 2021)
This research is based on the results of initial observations where some children still cannot control their emotions, which can be seen during the process of learning activities that there are still many children who are not enthusiastic about learning and do not have an attitude of responsibility towards themselves in carrying out various activities for their good. This research method uses Classroom Action Research (CAR). The subjects in the implementation of this study were group B children totaling 9 children for the 2019/2020 Academic Year. Data collection techniques in this study through observation and performance. The results showed that the activity of listening to relaxation music can increase the emotional intelligence of children in group B TKQ-Huda Antapani Bandung. This can be seen from the average result of teacher activity in the first cycle of 65.78% with a sufficient predicate and the second cycle, the average is 89.47% with a very good predicate. Furthermore, the results of children's activities in the first cycle were 44.44 % with the predicate less once, and in the second cycle, the average value was 82.40% with the good predicate. The average value of children's emotional intelligence in the first cycle is 31.66 with a very poor predicate and the average value in the second cycle is 74.06 with a good predicate. Based on the results obtained, it is evident that the activity of listening to relaxation music can increase the emotional intelligence of children in group B of TKQ Al-Huda Antapani Bandung.